Analysis of methods of receiving curv-lineary forms - Hrytsak, Stepan (Forestry, Forest, Paper and Woodworking Industry, 2017)
Four ways of obtaining curvilinear blanks are analyzed. It is indicated that obtaining curvilinear blanks by bending the whole wood is the most accepted variant in terms of rational use of the resource, technical and economic indicators and the scheme of organization of the technological process. However, the technological possibilities of obtaining the maximum ratio of thickness (h) of the workpiece to the bending radius (R) for different breeds are known and completely exhausted. To achieve smaller bending radii, combined with bending in different planes, it is possible with the prior modification of wood by compression along the fibers. However, there is no information on the physico-mechanical and rheological characteristics of such wood, as well as on the technological parameters of its obtaining. This contributes to the need for research in this direction.